Pimecrolimus 1% cream, methylprednisolone aceponate 0.1% cream and metronidazole 0.75% gel in the treatment of seborrhoeic dermatitis: A randomized clinical study - Cicek, Demet; Kandi, Basak; Bakar, Selma; Turgut, Dilara (Taylor & Francis Ltd, 2009)
Background: Seborrhoeic dermatitis is a common, chronic, papulosquamous dermatosis. Treatment of seborrhoeic dermatitis includes topical treatments such as corticosteroids, antifungals, metronidazole and pimecrolimus. Objective: This study aimed to compare and contrast the efficacy and tolerability of pimecrolimus cream 1%, methylprednisolone aceponate 0.1% cream and metronidazole 0.75% gel topical treatments in the treatment of facial seborrhoeic dermatitis. Methods: The study included a total of 64 (32 males and 32 females) consecutive patients with facial seborrhoeic dermatitis. Patients were randomized into three equal groups. One group applied pimecrolimus 1% cream, another group applied methylprednisolone aceponate 0.1% cream, and the third group applied metronidazole 0.75% gel to their facial lesions twice daily for 8 weeks. Assessment of the disease severity was performed at baseline and at weeks 2, 4, and 8. Clinical measures assessed were erythema, scaling and pruritus, which were evaluated using a four-point scale (0-3). Results: Of the 64 patients, 17 (80%) in the metronidazole group, 21 (100%) in the pimecrolimus group and 22 (100%) in the methylprednisolone aceponate group completed the study. Four patients in the metronidazole group left the study. All of the therapeutic agents were found to be effective; however, the efficacy of pimecrolimus was higher than those of metronidazole and methylprednisolone (p < 0.05). When side effects associated with pimecrolimus and metronidazole were compared, the latter was found to be associated with more side effects (p < 0.05). Conclusions: We suggest pimecrolimus to be a therapeutic option for seborrhoeic dermatitis cases that show an unfavourable response to methylprednisolone aceponate.
Keywords: methylprednisolone aceponate; metronidazole; pimecrolimus; seborrhoeic dermatitis